Effectiveness of Using The Wordwall Application on Student Learning Outcomes - Edy Susanto; Meilida Eka Sari (Institut Agama Islam Negeri Bengkulu, 2023)
Abstract: Effectiveness Of Using The Wordwall Application On Student Learning OutcomesThis study aims to describe the effectiveness of using the wordwall application on student learning outcomes of Madrasah Ibtidaiyah Teacher Education Study Program for Mathematics MI. This research method is descriptive quantitative experiment. The design to be used is Design One Pretest-Posttest Group. The subjects of this study were 31 students of the Al-Azhaar Lubuklinggau Islamic Elementary School Teacher Education Study Program. The instrument used is 25 multiple choice questions, the instrument has been tested for validity and reliability. The analysis technique used is the normality test and hypothesis testing. The results of the study by testing the paired sample test showed that the asym sig. (2-laid) of 0.00 <0.05 so that H_O is rejected and H_a is accepted, which means that there is an effectiveness of the application of the wordwall application on student learning outcomes of Madrasah Ibtidaiyah Teacher Education Study Program for Mathematics MI. It can be concluded that wordwall learning media (X) has a significant effect on student learning outcomes of the Al-Azhaar Lubuklinggau Islamic Institute of Islamic Religion (IAI) Teacher Education Study Program.Abstract: Efektivitas Menggunakan Aplikasi Wordwall Tentang Hasil Belajar Siswa.Penelitian ini bertujuan untuk mendeskripsikan efektivitas penggunaan aplikasi wordwall terhadap hasil belajar mahasiswa Prodi Pendidikan Guru Madrasah Ibtidaiyah Mata kuliah Matematika MI. Metode penelitian ini adalah deskriftif kuantitatif eksprimen. Desain yang akan digunakan adalah Design One Grup Pretes-Posttest. Subjek penelitian ini adalah 31 mahasiswa Prodi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau. Instrumen yang digunakan yaitu 25 butir soal pilihan ganda, instrument tersebut telah dilakukan uji validitas dan uji reliabilitas. Teknik analisis yang digunakan adalah uji normalitas, dan uji hipotesis. Hasil penelitian dengan pengujian paired sampel test menunjukan bahwa nilai asym sig. (2-lailed) sebesar 0,00 < 0,05 sehingga Â ditolak dan Â diterima yang artinya adanya efektivitas penerapan aplikasi wordwall terhadap hasil belajar mahasiswa Prodi Pendidikan Guru Madrasah Ibtidaiyah Mata kuliah Matematika MI. Dapat disimpulkan bahwa media pembelajaran wordwall (X) berpengaruh signifikan terhadap hasil belajar mahasiswa Prodi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau.Â